(untitled) (Research, Society and Development, 2021)
Endodontic treatment aims to remove infected tissues and microorganisms from the root canal system (RCS). Due to the complexity of SCR, conventional irrigation methods and become limited, so different techniques were introduced in order to enhance cleaning and disinfection of them. The objective of this experiment was to compare the intracanal microbial reduction promoted by conventional endodontic treatment and photodynamic therapy (PDT) with laser emission at the entrance and inside the root system. The present study included patients according to some inclusion criteria and they were distributed in groups as described: in groups G1(10) following the chemical preparation protocol (CPP), G2(10) with CPP+PDT protocol with tips at the entrance of the canal and G3(10) in the SCP+PDT protocol with a tip inside the canal. Two-way ANOVA test p>0.05 was performed for comparison between groups. The results showed a microbial reduction in all groups, but there was no significant difference between them. There was greater homogeneity of data in the irradiated groups (G2 and G3) than G1. It is concluded that PDT can be used as an adjunct to endodontic treatment with an increase in its success rate.